Effect of oil type and concentration on solid fat contents and rheological properties of watery oleogels - Pehlivanoglu, Halime; Akcicek, Alican; Can, Asli Muslu; Karasu, Salih; Demirci, Mehmet; Yilmaz, Mustafa Tahsin (INNOVHUB SSI-AREA SSOG, 2021)
This study aims at evaluating the effect of oil type and concentration on solid fat contents and rheological properties of oleogels (OGs) prepared using different types of oils; namely, HOSO (High oleic sunflower oil), HO (Hazelnut oil), OO (Olive oil) and BF (Blend Fat) as well as food-grade carnauba wax (CW) as an oleogelator at different concentrations (5 and 7%). The rheological analysis showed that all OGs samples exhibited viscoelastic solid-like gel behaviour. Both oil and wax concentrations significantly (p<0.05) affected the viscoelastic rheological properties. K' values of the samples increased with increased wax and aqueous phase concentration. The type of oils and their ratio in an oil phase could significantly (p<0.05) affect the K' values and solid fat content (SFC). At 5% of wax concentration, the sample A4 prepared with 100% HOSO had the lowest SFC at all temperature levels. At 7% of wax concentration, the sample C3 prepared with 100% HOSO had the lowest SFC at the temperature levels ranging between 10 and 30 degrees C; however, the sample (coded as B4) prepared with 100% HOSO had the lowest SFC at 35 degrees C. These results suggest that wax/OGs blends could be produced by using wax and different types of oils at different concentrations. The use of oleogels could be further suggested in terms of healthy nutrition given the possibility to decrease the level of saturated fatty acids in people's diet.
Keywords: Oleogels; viscoelastic properties; margarine; wax; RICE BRAN WAX; CANDELILLA WAX; ETHYLCELLULOSE OLEOGELS; MECHANICAL-PROPERTIES; SATURATED FAT; OLIVE OIL; QUALITY; REPLACEMENT; ORGANOGELS; BEHAVIOR; Food Science & Technology